Stability, Specialisation and Divergence in Export Patterns for EU15 - Ufuk Gunes Bebek (University of Kent, School of Economics, 2011)
This paper examines the extent of stability, specialisation and divergence in manufacturing industries' export patterns for EU15 countries at both industry and country level, distinguishing between intra and extra EU15 exports as well as different technological categories. Both countrywide and industrywide analyses suggest that specialisation patterns, on average, are rather sticky. Furthermore, as proposed, intra-EU15 specialisation patterns are less persistent, particularly in higher technology industries. From an industry specific point, such non-persistence within intra-EU15 patterns is reflected as convergence of countries, whereas persistent extra-EU15 patterns are reflected as divergence of countries, which again are more common in higher technology industries.
Keywords: F11; F14; O52; 330; Specialisation; Convergence; Comparative Advantage